2018
DOI: 10.1021/acssuschemeng.7b04424
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effect in Hydrogenolysis of Xylitol over Bifunctional Ru/MnO/C Catalysts under Alkaline-Free Conditions

Abstract: The hydrogenolysis reaction of biomass-derived xylitol to glycols and glycerol has been carried out in different aqueous solvents over a bifunctional Ru/MnO/C catalyst under alkaline-free conditions at 60 bar H 2 and 200°C. In pure water, the retro-aldol reaction takes place. However, decarbonylation and epimerization are the dominant reactions and produce C4 and C5 alditols, which limits the overall selectivity to glycols and glycerol (30%). When 90:10 vol.% water:1,4dioxane and water:2-PrOH solutions are use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 41 publications
2
23
0
1
Order By: Relevance
“…The Ru-(Mn-Zn)O X material was not active at all and no conversion was measured after a reaction time of 30 h. A comparable result was observed in our previous study using Ru/ZnO/C catalyst; the catalytic activity decreased from 220 to 13 h −1 in comparison with Ru/MnO/C catalyst [25]. Yet, previous studies have reported that the combination of Cu and ZnO was active and selective in the hydrogenolysis of alditols to glycols [21,[36][37][38].…”
Section: Hydrogenolysis Of Xylitolsupporting
confidence: 86%
See 4 more Smart Citations
“…The Ru-(Mn-Zn)O X material was not active at all and no conversion was measured after a reaction time of 30 h. A comparable result was observed in our previous study using Ru/ZnO/C catalyst; the catalytic activity decreased from 220 to 13 h −1 in comparison with Ru/MnO/C catalyst [25]. Yet, previous studies have reported that the combination of Cu and ZnO was active and selective in the hydrogenolysis of alditols to glycols [21,[36][37][38].…”
Section: Hydrogenolysis Of Xylitolsupporting
confidence: 86%
“…Moreover, the products transferred into the gas phase (determined as the difference of initial TOC and TOC measured in the liquid phase) were produced in lower amounts over Ru-(Mn-Al)O X . This observation suggests that the side reactions of cascade decarbonylation leading to the degradation of glycols, particularly EG, were minimized [25]. This was confirmed by the calculation of the molar ratio of C 3 to C 2 products, which was 1.3 and 1.9 for the reactions in the presence of Ru-(Mn-Al)O X and Ru/(Mn-Al)O X , respectively, while the theoretical molar ratio is 1.0 for a totally selective hydrogenolysis reaction of xylitol to EG plus PG.…”
Section: Hydrogenolysis Of Xylitolmentioning
confidence: 92%
See 3 more Smart Citations